Design and Prototyping High Endurance Multi-Rotor - Gatti, Mauro <1977> (Alma Mater Studiorum - Università di Bologna, 2015)
The topic of this thesis fo cus on the preliminary design and the p erformance analysis of a multirotor platform. A multirotor is an electrically p owered Vertical Take Off (VTOL) machine with more than two rotors that lift and control the platform. Multirotor are agile, compact and robust, making them ideally suited for b oth indo or and outdo or application especially to carry-on several sensors like electro optical multisp ectral sensor or gas sensor. The main disadvantage is the limited endurance due to heavy Li-Po batteries and high disk loading through the use of different small prop ellers. At the same time, the design of the multirotor do es not follow any engineering principle but it follow the ideas of amateurs’ builder. An adaptation of the classic airplane design theory for the preliminary design is implemented to fill the gap and detailed study of the endurance is p erformed to define the right way to make this kind of VTOL platforms.